Lungen- und Nierenversagen - Pathogenese, Wechselwirkungen und Therapie - John, Stefan; Willam, Carsten (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2015)
The lungs and kidneys represent the most often affected organs (acute respiratory distress syndrome, ARDS or kidney failure) in multiple organ failure (MOF) due to shock, trauma, or sepsis with a still unacceptable high mortality for both organ failures.Although the exact pathophysiological mechanisms of MOF are not completely elucidated, it appears that the lungs and kidneys share several pathophysiologic pathways and have the potential to further harm each other (kidney-lung crosstalk). Inflammatory signals in both directions and volume overload with consecutive edema formation in both organs may play a key role in this crosstalk.The organ replacement therapies used in both organ failures have the potential to further injure the other organ (ventilator trauma, dialyte trauma). On the other hand, renal replacement therapy can have positive effects on lung injury by restoring volume and acid-base homeostasis. The new development of "low-flow" extracorporeal CO2 removal on renal replacement therapy platforms may further help to decrease ventilator trauma in the future.
EVALuna2:3745